2017
DOI: 10.7150/jbm.17492
|View full text |Cite
|
Sign up to set email alerts
|

Aligning Effectiveness, Secretion of Interleukin 1β and Pain Control During Fixed Orthodontic Treatment with Self-Ligating Appliances and Supplemental Vibrational Appliances. A Randomized Controlled Clinical Trial

Abstract: Aims: The aims of the present study were to investigate rate of mandibular incisors alignment, levels of IL-1β and pain and discomfort during orthodontic alignment with the following: 1) conventional-ligating appliance (CLA); 2) self-ligating appliance (SLA); 3) self-ligating appliance combined to vibrational appliance (SLA-VA). Methods: This was a three-armed parallel group randomized clinical trial with allocation ratio 1:1:1. The main inclusion criteria were: full permanent dentition, age below 25 years, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 26 publications
(36 reference statements)
0
24
0
Order By: Relevance
“…The increase in IL-1 levels occurred both by direct and indirect applications of mechanical force to the teeth. A similar study concerning the determination of IL-1β concentrations in GCF from the fissure of lower incisal teeth in patients during orthodontic treatments with self-ligating braces was conducted by Kalemaj et al [38].…”
Section: Discussionmentioning
confidence: 88%
“…The increase in IL-1 levels occurred both by direct and indirect applications of mechanical force to the teeth. A similar study concerning the determination of IL-1β concentrations in GCF from the fissure of lower incisal teeth in patients during orthodontic treatments with self-ligating braces was conducted by Kalemaj et al [38].…”
Section: Discussionmentioning
confidence: 88%
“…In vitro studies [27][28][29][30][31] and different in vivo studies [32][33][34][35][36][37] ) conducted in the past using various biomarkers and vibration devices have reported mixed results.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the study has an overall high risk of bias. Kalemaj et al 34 conducted a 3-armed parallel group RCT with the allocation ratio of 1:1:1. A sample of 33 patients was randomly categorized into 3 groups (conventional ligating appliance group, self-ligating appliance group, and selfligating appliance with accledent group).…”
Section: Continued)mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have reported how dental anxiety is an understudied problem and have underlined the importance of implementing strategies to overcome such a common problem for both children and adult patients (2)(3)(4). Attempts to control dental pain and discomfort include a wide variety of psychological therapies and mechanical strategies, depending mainly on the type of dental treatment and structure of dental anxiety (5,6). Among the fear provoking objects, the sight and sensation of anesthetic needle remains one of the most relevant (7,8).…”
Section: Introductionmentioning
confidence: 99%